Land use in dolomite regions in Slovenia - Gabrovec, Matej (Acta carsologica, 1995)
The dolomite surfaces in Slovenia cover approximately 2400km2, which is 12% of the territory of the Republic of Slovenia. Most of the dolomites are of Triassic age and a tenth of Iurassic or Cretaceaus age. Most of the dolomite regions differs greatly from the one of the karst limestone and the non-karst areas. A high percentage of meadow areas, which can be often found on very steep slopes, is rather typical. A growing number of steep meadows and pastures has lately been abandoned. Thus, it is the dolomite regions that takethe biggest share of surfaces which are in the process of being overgrown.
Keywords: dolomit; kras (geologija); pedogeografija; pedologija; Slovenia; Slovenija; tla